Ocular and General Proprioception in Dyslexic Children: A Review of Their Diurnal and Nocturnal Dysfunctions and Their Repercussions - Patrick Quercia; Kalvin Chavet; Jérémie Gaveau (Vision, 2025)
We provide a summary of the research conducted in our laboratory on the relationship between ocular proprioception, general proprioception, and dyslexia. Dyslexic children show a marked proprioceptive deficit which affects motor control, attention and spatial perception. The spatial disturbances are expressed by the presence of a vertical microheterophoria which has very specific characteristics. It is associated with abnormal tone of the oblique muscles and can be modified by means of very low powered prisms and/or remote sensory stimulation. When ocular proprioception is modified, sounds cause stochastic visual losses. This may interfere with the association between phonemes and graphemes, which is necessary for learning to read. The effects of a generalized nocturnal proprioceptive disorder may play a role in the abnormal brain development that has been observed in dyslexic children.